2012
DOI: 10.1177/1470320312459980
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren alleviates doxorubicin-induced nephrotoxicity by inhibiting oxidative stress and podocyte injury

Abstract: Introduction: Doxorubicin (DXR) is one of the most effective and widely used anthracycline antibiotics. However, its clinical application is hampered by toxic effects in many organs. Nephrotoxicity is one of the major side effects of anthracycline antibiotics. This study was designed to investigate the possible protective effects of aliskiren (a direct renin inhibitor) in DXR-induced nephrotoxicity in rats. Materials and methods: Wistar albino rats were intraperitoneally (ip) injected with DXR and renin activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
12
20
0
Order By: Relevance
“…So far, there only a few studies investigating about the effect of aliskiren on ADR-induced nephrotoxicity have been published. 19,30,41 They reported that plasma renin activity increased in rats with ADR-induced nephrotoxicity. They also found that ADR-induced nephrotoxicity was manifested by elevation in the plasma levels of BUN and creatinine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, there only a few studies investigating about the effect of aliskiren on ADR-induced nephrotoxicity have been published. 19,30,41 They reported that plasma renin activity increased in rats with ADR-induced nephrotoxicity. They also found that ADR-induced nephrotoxicity was manifested by elevation in the plasma levels of BUN and creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…However, ADR treatment has been shown to activate the renin angiotensin system (RAS). 19,[29][30][31] Furthermore, the effectiveness of blockade of the reninangiotensin system in slowing the progression of proteinuria of kidney diseases is well recognized. Therefore, we investigated the interaction between the RAS and the ADR nephrotoxicity in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chemotherapeutic agent was found to produce a significant increase in malondialdehyde and a significant inhibition in the activity of glutathione in heart tissue, with a significant rise in the serum levels of lactate dehydrogenase (LDH), TC, triglycerides (TG), LDL and reduction in HDL. Fortunately, this pretreatment with aliskiren provides a protection against all these side effects of DXR with strong evidence evidence that aliskiren pretreatment offered a significant cardio-protection against DXR-induced enzymatic changes and cardiac tissue damage [33].…”
Section: Discussionmentioning
confidence: 99%
“…A new drug of renin angiotensin system (RAS) inhibitors (aliskiren (AL)) is a direct inhibitor of the renin enzyme (Rashikh et al 2012) and is reported to be cardioprotective against acute ADR-induced toxicity in heart (Rashikh et al 2013b) and kidney . In other words, the blockade of the renin activity by aliskiren might be a promising approach in the treatment of ADR-induced toxicity (Rashikh et al 2013a).…”
Section: Introductionmentioning
confidence: 99%